The Impact of Career Development, Work-Family Conflict, and Job Satisfaction on Millennials’ Turnover Intention in Banking Industry - Shirley Elian; Cindy Diva Paramitha; Hendra Gunawan; Anita Maharani (Profesional Muda Cendekia Publishing, 2020)
With a strong domination of the Millennials generation in the workforce, they become one of the key holders in the success of the organisation and the economy. Their behaviour of working short tenure and job-hop worries many organisations as this halt the organisations’ growth, performance and productivity while also incurring extra costs. Banking sector is known to have a high turnover rate and has been lacking in the number of talents which delays their implementation on key strategic initiatives. It becomes important to study the factor influencing the Millennials turnover rate. This study aims to measure the influence of Career Development (CD), Work-family Conflict (WFC), and Job Satisfaction (JS) on Millennials Turnover Intention (TI) in Indonesia’s banking industry. A quantitative research is conducted among Indonesia's Millennials banking employees and data were analysed using PLS-SEM. The result shows that Work-family Conflict has a significant positive direct impact on Turnover Intention. Job Satisfaction is also observed to have a significant negative direct impact towards Turnover Intention. Interestingly, Career Development has no direct significant impact on Turnover Intention unless it is mediated by Job Satisfaction. However, Work-family Conflict has no effect on Turnover Intention if it is mediated by Job Satisfaction. Additionally, this research provides academic and practical implications on how to manage these Millennials to reduce Turnover Intention in the banking industry which could lead to an actual turnover.